Structure and functional diversity of microbial communities in tundra soils in different degrees of degradation - Arna Björt Ólafsdóttir 1989- (2023)
In Iceland, unsustainable land use has led to severe land degradation and desertification. Although some indicators of land degradation, such as changes in plant community compo-sition or increases in the amount of bare ground, are well established, limited knowledge exists on soil microbial communities and their function in degraded ecosystems. This study aimed to characterize the structure and function of microbial communities using shotgun metagenomic sequencing in contrasting stages of degradation in the highlands of Iceland. I compared a Betula nana heath with erosion spots and a highly degraded desert within a three-year-old exclosure experiment inside and outside the active volcanic zone, at Þeistar-eykir and Auðkúluheiði. The desert soil’s bacterial taxonomic composition (relatively more Actinobacteria), low respiration (microbial activity) and functional diversity reflected its highly degraded state. Heath soils at Þeistareykir, had more abundant key ecosystem taxa of the genus Bradyrhizobium, higher taxonomic richness, microbial activity, and functional diversity compared to the heath at Auðkúluheiði, which indicates that the heath in Auðkúluheiði is more degraded. The use of the trait-based framework of high yield (Y), resource acquisition (A), and stress tolerance (S) provided a more nuanced picture of the functional microbial roles in each of these soil types. Three years of exclusion of grazing, the hypothesised main driver of the degradation of highland ranges, was apparently too short for significant recovery of the soil bacterial community. This study presents for the first time a characterization of soil microbial communities in different tundra soils in Ice-land and shows promise in identifying degradation processes. Á Íslandi hefur átt sér stað víðtæk jarðvegseyðing af völdum ósjálfbærrar landnýtingar. Í vistkerfum hálendisins þar sem beitarálag er talinn vera meginorsök hnignunar hefur ástand lands (stig hnignunar) verið metið út frá gróðurþekju, gróðursamsetningu, og umfangi rofdíla. ...